The age of detrite zircon from metasedimentary rocks of the Ternuvate strata (West Azov block of the Ukrainian Shield) - Artemenko, G.V.; Shumlyanskyy, L.V.; Dovbysh, L.S. (Доповіді НАН України, 2023)
The Ternuvate strata comprise metamorphic rocks that make up the Haichur arcuate structure, which is about 72 km
long. Its western part lies within the Andriivka fault zone, which separates the Vovcha and Huliaipole blocks, while the
eastern part is located within the Ternuvate fault zone, traced on the Remivka block. The rocks composing the Haichur
structure have irregular and laterally variable composition, changeable thickness, and exhibit dynamometamorphic
structures of boudinage and schistosity. The upper part of the Ternuvate strata mainly consists of metasedimentary
rocks, including gneisses, biotite schists, garnet-biotite, magnetite-amphibole, and feldspar quartzites. The lower part
comprises volcanogenic rocks such as amphibolites, metaultrabasites, and biotite-amphibole gneisses. Using the LAICP-
MS method, 38 zircon crystals from muscovite-biotite gneisses in the upper part of the Ternuvate strata were
analyzed. Based on the geochemical data, these zircons are metamorphosed graywackes. The zircon crystals belong
to several age populations (3.65-3.45 and 3.3-2.95 Ga), corresponding to the major stages of Archean crust formation
in the West Azov domain, including the formation of the oldest basement and granite-greenstone complexes of the
Paleoarchean and Mesoarchean ages. Identical populations of detrital zircon were found in the early Precambrian
metaterrigenous rocks of the Krutobalka Formation in the Sorokyne greenstone structure. The correspondence between
the Paleoarchean crust (3.45-3.65 Ga) of the West Azov block of the Ukrainian Shield and the Kursk-Besedine granulitegneiss
area of the Kursk Magnetic Anomaly block is evident, while the Paleoarchean and Mesoarchean complexes (2.9-
3.3 Ga) correspond to the Mykhailivka and Orel-Tim granite-greenstone area of the Kursk Magnetic Anomaly block.
The Archean complexes of Sarmatia are of the same age as similar formations in the Kaapvaal craton in South Africa,
Bastar craton in India, North China Craton, Slave craton in Canada, and others, which formed during the Eoarchaean. Тернуватська товща метаморфічних порід складає Гайчурську структуру дугоподібної форми завдовжки
близько 72 км. Її західна частина знаходиться в зоні Андріївського розлому, який розділяє Вовчанський та
Гуляйпільський блоки, а східна — у зоні Тернуватського розлому на Ремівському блоці. Породи, що формують Гайчурську структуру, характеризуються строкатим та мінливим по латералі складом та змінною
потужністю, в них спостерігаються динамоструктури — розлінзування та розсланцювання. Верхня світа
тернуватської товщі складена переважно метаосадовими породами — гнейсами та сланцями біотитовими,
гранат-біотитовими, глиноземистими, магнетит-амфіболовими та польовошпатовими кварцитами. Ниж-
ня світа представлена вулканогенними породами — амфіболітами, метаультрабазитами та гнейсами біотит-амфіболовими. Методом LA-ICP-MS було продатовано 38 кристалів циркону з мусковіт-біотитових
гнейсів верхньої світи тернуватської товщі, які за петрохімічними даними відповідають метаморфізованим граувакам. Серед них виявлено три популяції циркону — 3,65—3,45; 3,3 і 3,2—2,95 млрд років, які відповідають трьом етапам формування архейської кори Західноприазовського домену: утворенню найдавнішого фундаменту та граніт-зеленокам’яних комплексів палеоархейського і мезоархейського віку. Згідно з
результатами зіставлення породних асоціацій Українського щита та Курської магнітної аномалії, очевидна
відповідність палеоархейської кори (3,45—3,65 млрд років) Західноприазовського блока і Курсько-Бесединської грануліт-гнейсової області, а палеоархей-мезоархейські комплекси (2,9—3,3 млрд років) відповідають Михайлівській і Орловсько-Тимській структурам граніт-зеленокам’яної області Курської магнітної
аномалії. Архейські комплекси Сарматського континенту є одновіковими з подібними утвореннями кратону Каапвааль у Південній Африці, Бастар в Індії, Північно-Китайського кратону, кратону Слейв у Канаді та інших, що формувалися починаючи з еоархею.